2014
DOI: 10.1186/1471-2474-15-66
|View full text |Cite
|
Sign up to set email alerts
|

Self-perceived weather sensitivity and joint pain in older people with osteoarthritis in six European countries: results from the European Project on OSteoArthritis (EPOSA)

Abstract: BackgroundPeople with osteoarthritis (OA) frequently report that their joint pain is influenced by weather conditions. This study aimed to examine whether there are differences in perceived joint pain between older people with OA who reported to be weather-sensitive versus those who did not in six European countries with different climates and to identify characteristics of older persons with OA that are most predictive of perceived weather sensitivity.MethodsBaseline data from the European Project on OSteoArt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
44
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 22 publications
3
44
0
1
Order By: Relevance
“…In Sweden, 74% of people agreed that "local sport clubs and other providers offer many opportunities for physical activity," compared to 54% in Italy (37). Finally, environmental conditions such as local climate have been found to affect pain perceptions in persons with OA (38), with a greater impact in Southern Europe. In summary, contextual factors seem to influence individuals' behavior when it comes to coping with their disease and influence whether they can build up a physically active lifestyle.…”
Section: Discussionmentioning
confidence: 99%
“…In Sweden, 74% of people agreed that "local sport clubs and other providers offer many opportunities for physical activity," compared to 54% in Italy (37). Finally, environmental conditions such as local climate have been found to affect pain perceptions in persons with OA (38), with a greater impact in Southern Europe. In summary, contextual factors seem to influence individuals' behavior when it comes to coping with their disease and influence whether they can build up a physically active lifestyle.…”
Section: Discussionmentioning
confidence: 99%
“…Such ideas persisted until the eighteenth century (e.g., Miller 1962;Janković 2010, chapter 1). Today, a common belief among three-quarters of patients who suffer from chronic pain is that their daily pain levels fluctuate with the weather (e.g., Hagglund et al 1994;Timmermans et al 2014).…”
mentioning
confidence: 99%
“…1,50 Higher levels of anxiety and depression have also been found to be predictors of weather sensitivity. 51 Likewise, there is overwhelming evidence that pain is influenced by mood disorders. [52][53][54][55][56] Past scholars have suggested a mediating relationship such that weather affects mood and, in turn, mood affects pain.…”
Section: Discussionmentioning
confidence: 99%
“…64 Other studies investigating military personnel have found the most frequently reported reason for missing appointments was administrative error (including believing their appointment was on another date, having cancelled the appointment, and not knowing they had an appointment). 65 Furthermore, due to limitations of this archival collection, demographics (e.g., gender differences 15,51 ) and other individual barriers to care (e.g., distance from the facility and/or finances 66 ) were not able to be assessed. Future studies would benefit from controlling for these variables to better understand the unique contribution of weather on treatment compliance for those with chronic pain conditions.…”
Section: Discussionmentioning
confidence: 99%